2014
DOI: 10.1080/17461391.2014.936322
|View full text |Cite
|
Sign up to set email alerts
|

Minimalist, standard and no footwear on static and dynamic postural stability following jump landing

Abstract: In recreational sports, uncushioned, light-weight and minimalist shoes are increasingly used to imitate barefoot situations. Uncertainty exists whether these shoes provide sufficient stability during challenging movements. In this randomised crossover study, 35 healthy distance runners performed jump landing stabilisation and single-leg stance tests on a force plate, using four conditions in random order: barefoot, uncushioned minimalist shoes, cushioned ultraflexible shoes and standard running shoes. Ground r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
(36 reference statements)
0
19
1
Order By: Relevance
“…Prior to this study, only one other study had examined the influence of different types of running footwear on dynamic stability. In that study Zech, et al found no effect of footwear on dynamic postural stability during single-leg landings [33]. One potential reason for the difference between our findings and those reported by Zech, et al may be due to the dynamic stability measure used.…”
Section: Discussioncontrasting
confidence: 86%
See 4 more Smart Citations
“…Prior to this study, only one other study had examined the influence of different types of running footwear on dynamic stability. In that study Zech, et al found no effect of footwear on dynamic postural stability during single-leg landings [33]. One potential reason for the difference between our findings and those reported by Zech, et al may be due to the dynamic stability measure used.…”
Section: Discussioncontrasting
confidence: 86%
“…These baseline values are reported to have a propensity to be influenced by group differences in postural sway during quiet standing creating unequal group comparisons [29]. This poses a problem for Zech, et al who reported significant differences in postural sway during quiet standing among footwear conditions [33]. It is possible that the differences in postural sway during quiet standing reported by Zech, et al could have impacted their ability to find significant differences for dynamic stability utilizing the TTS measure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations